The role of seeding in the morphology and wettability of ZnO nanorods films on different substrates - Rodríguez, Juan (2013)
This work was supported by the Peruvian-Argentinean 321-2009-CONCYTEC OAJ Project and MINCYT-CONCYTEC PE/09/01 and PE/11/02